Implementation Of Insurance Agreements In The Compensation Services For Accident Victims At PT Jasa Raharja Central Sulawesi - Andi Auliyah Nurul; Annisa Wahdania; Yolanda Mitalova Ule; Abdul Kahar; Ernawaty Usman (Universitas Dehasen Bengkulu, 2026)
This research examines the deconstruction and evaluative analysis of the implementation of social insurance engagement principles in compensation services for traffic accident victims at PT Jasa Raharja Central Sulawesi Branch. The study employs an empirical juridical method with a descriptive qualitative approach, integrating field data through in-depth interviews as well as legal document and statistical studies. The findings indicate that compensation services are based on the principle of absolute liability, supported by a multi-tiered verification system to ensure the accountability of public funds. Digital transformation through the JR-Care, DASI-JR, and IRSMS platforms has accelerated the average settlement time for death claims to 1 day and 9 hours, while also achieving a 100 percent cashless overbooking rate. Geographical challenges along the extreme Kebun Kopi route and the public’s low level of legal literacy regarding the six-month claim expiration period remain the primary obstacles. Strengthening cross-sectoral coordination, implementing ISO 27001 standards, and fraud mitigation through a postpaid program are key factors in realizing distributive justice for the people of Central Sulawesi.